L. acidophilus La-5, fructo-oligosaccharides and inulin may improve sensory acceptance and texture profile of a synbiotic diet mousse. (May 2019) - Xavier-Santos, Douglas; Bedani, Raquel; Perego, Patrizia; Converti, Attilio; Saad, S.M.I.
Abstract: We evaluated in this study the effects of Lactobacillus acidophilus La-5, fructo-oligosaccharides (FOS) and inulin supplementation as well as time of storage at −18 °C on sensory acceptance and instrumental texture profile of a synbiotic diet mousse (SDM) compared with a standard mousse without pro- and prebiotics. Formulations were compared in terms of chemical composition, total energy value, pH variation, instrumental texture profile (hardness, adhesiveness, elasticity, cohesiveness, and gumminess), and sensory acceptability. L. acidophilus La-5 counts in SDM remained above 7.8 log CFU g −1 during 112-day storage, with no significant differences (p > 0.05) in its viability. SDM pH throughout storage was slightly lower than that of standard mousse, and its total energy value about 20% lower. SDM gumminess and hardness increased, adhesiveness and springiness remained relatively stable, while cohesiveness decreased along storage. Standard mousse showed lower acceptability after storage than SDM, probably due to its higher content of powdered milk and absence of inulin and FOS. These results suggest that the presence of L. acidophilus La-5 and prebiotics may improve texture and sensory properties of diet mousses. Highlights: L. acidophilus, inulin and fructooligosaccharide are used in a synbiotic diet mousse. L. acidophilus count in synbiotic mousse is maintained after the storage period. Synbiotic mousse has total energy value about 20% lower than non-synbiotic mousse. Synbiotic diet mousse shows higher sensory acceptability than non-synbiotic mousse.